Unbound voices : a documentary history of Chinese women in San Francisco - Yung, Judy (University of California Press, 1999)
Unbound Voices brings together the voices of Chinese American women in a fascinating, intimate collection of documents--letters, essays, poems, autobiographies, speeches, testimonials, and oral histories--detailing half a century of their lives in America. Together, these sources provide a captivating mosaic of Chinese women's experiences in their own words, as they tell of making a home for themselves and their families in San Francisco from the Gold Rush years through World War II.